Designed Complex Peptide‐Based Adaptive Systems: A Bottom‐Up Approach. Issue 1 (24th November 2022) - Kassem, Salma; Ulijn, Rein V.
Abstract: Systems chemistry represents a shift from studying molecules in isolation to studying the collective behavior of mixtures or ensembles of reacting and interacting molecules. This research direction provides new ways to build and understand collective chemical properties and emergent functions that are inaccessible using conventional, reductionist, chemistry approaches. This field exemplifies fundamental connections between chemistry and biology, and has the potential to give rise to completely new ways for chemists to approach and resolve wide‐ranging issues related to all aspects of living systems, that themselves are complex systems. Short peptides, while simple in design, carry rich and versatile information encoded in sequence specific side‐chain interactions, that makes it possible to access a high level of complex, information rich systems with emergent properties from Life's simplified building blocks. This review focuses on recent developments in the synthesis of complex adaptive systems based on peptides, where multiple components are designed to cooperatively interact, react and collectively adapt to their context. Abstract : Combinatorial adaptive systems : Mixtures of components (grey) react to produce new interconvertible products (blue) in a reversible way. Product distribution is determined by their relative stability which is dictated by their participation or not in cooperative stabilizing interactions. Product distribution is condition specific and adapts to changes by downregulation and amplification of products.